Performance Evaluation of Outdoor High Voltage Glass Insulators in High Pollution Industrial Areas Using Simulated Acid Rain Contamination - Chibuike Ilomuanya; Shahab Farokhi; Azam Nekahi (IEEE Access, 2022)
A suitable, non-standard method for artificial pollution testing using simulated acid rain pollution in a laboratory was developed in this work. The method is applicable to a wide range of climatic conditions and rain acidities. The established method adopts the solid layer principle in the preparation and application of acid rain of various pollution severities to test insulators. Glass cap and pin insulators were contaminated, assembled into strings of two discs and flashover tests carried out on the strings at different orientation angles. The frequency of flashover occurrence, maximum withstand degree of pollution, effect of pollution severity, and effect of orientation angle were investigated. Test results showed that the orientation angle plays little or no role in the flashover of the insulators under dry conditions. Under wet conditions, the insulators performed better when inclined. Flashover voltage was observed to be inversely proportional to time while the time to flashover was inversely proportional to the pollution severity. The probability of flashover increases with an increase in voltage for a fixed pollution severity or increase in pollution severity for a fixed voltage level. This indicates that the probability of flashover under the test condition is a function of pollution severity and voltage.